Environmental, Social and Governance (ESG) Committees and Performance in Thailand - Muttanachai Suttipun,; Parnicha Dechthanabodin, (Asian Journal of Business and Accounting, 2022)
Manuscript type: Research paper Research aims: The study aims to investigate the extent and level of environmental, social and governance (ESG) performance of listed companies in Thailand, and test for the relationship between ESG committees and performance. Design/methodology/approach: Using the top 100 Thai listed companies (364 firm-year observations) from the Stock Exchange of Thailand (SET), the corporate annual reports during 2018 to 2021 are used to collect ESG board committee characteristics, while ESG performance is collected and measured by ESG scores from S&P Capital IQ and Capital IQ Pro databases. Descriptive analysis, correlation matrix, and multiple regression are used to analyse the data. Research findings: The average performance score of ESG in Thailand is 29.52. In addition, there was an increase of ESG performance by the top 100 firms in Thailand during the period under study. There is a significantly positive relationship between independent ESG committees and ESG performance, while dual positions between top management and ESG committees is negatively correlated with ESG performance. Theoretical contribution/originality: The findings of the relationship between ESG committees and performance demonstrates that agency theory can be used to explain the factors influencing ESG performance by Thai listed companies.